Exploration of New Solitons for the Fractional Perturbed Radhakrishnan–Kundu–Lakshmanan Model - Kaplan, Melike; Alqahtani, Rubayyi T. (MDPI AG, 2023)
The key objective of the current manuscript was to investigate the exact solutions of the fractional perturbed Radhakrishnan–Kundu–Lakshmanan model. For this purpose, we applied two reliable and efficient approaches; specifically, the modified simple equation (MSE) and exponential rational function (ERF) techniques. The methods considered in this paper offer solutions for problems in nonlinear theory and mathematical physics practice. We also present solutions obtained graphically with the Maple package program.
Keywords: fractional partial differential equation; exact solutions; fractional partial differential equation; symbolic computation; mathematical models; nonlinear equations; nonlinear equations; QA1-939; exact solutions; mathematical models; symbolic computation; Mathematics